If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4w + -2)(5w + 4) = 0 Reorder the terms: (-2 + 4w)(5w + 4) = 0 Reorder the terms: (-2 + 4w)(4 + 5w) = 0 Multiply (-2 + 4w) * (4 + 5w) (-2(4 + 5w) + 4w * (4 + 5w)) = 0 ((4 * -2 + 5w * -2) + 4w * (4 + 5w)) = 0 ((-8 + -10w) + 4w * (4 + 5w)) = 0 (-8 + -10w + (4 * 4w + 5w * 4w)) = 0 (-8 + -10w + (16w + 20w2)) = 0 Combine like terms: -10w + 16w = 6w (-8 + 6w + 20w2) = 0 Solving -8 + 6w + 20w2 = 0 Solving for variable 'w'. Factor out the Greatest Common Factor (GCF), '2'. 2(-4 + 3w + 10w2) = 0 Factor a trinomial. 2((-4 + -5w)(1 + -2w)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-4 + -5w)' equal to zero and attempt to solve: Simplifying -4 + -5w = 0 Solving -4 + -5w = 0 Move all terms containing w to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -5w = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -5w = 0 + 4 -5w = 0 + 4 Combine like terms: 0 + 4 = 4 -5w = 4 Divide each side by '-5'. w = -0.8 Simplifying w = -0.8Subproblem 2
Set the factor '(1 + -2w)' equal to zero and attempt to solve: Simplifying 1 + -2w = 0 Solving 1 + -2w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2w = 0 + -1 -2w = 0 + -1 Combine like terms: 0 + -1 = -1 -2w = -1 Divide each side by '-2'. w = 0.5 Simplifying w = 0.5Solution
w = {-0.8, 0.5}
| 18m+27=2m-3 | | -4-6x=-64 | | y-5y= | | m(m+4)(m-7)=0 | | 3(3x-1)=4(4x-1) | | 4s+8=12 | | x+11=314.86 | | -14(9+19p)=3066 | | 12(x-7)=60 | | X^2+x=2 | | 4p^2-5pq= | | 252=x+.8x | | 3(y+7)=4(y-2) | | 3m-8m=10 | | 4=p+14 | | 3x^2(4x+5)(x-6)=0 | | -6(2p+2)-24=4(3p+3) | | 4p^4-5pq= | | 1-10x=-319 | | -3p+5p+4=6 | | 6n-6=18 | | 4x^2+12x+9= | | 12n-24=-14+28 | | (5x+15)(5x+15)=45 | | 6x^2+5x=4 | | -19(1-3k)-5k=553 | | 5.4x-4.3(x-1)=5.7 | | 2x^5-15x^4+32x^3+6x^2-60x=0 | | .875r+.25=.75+.375r | | 2(c-5)=3(c-6) | | 14(x-7)=42 | | -15+4x=-6(x+8)-x |